A mantidfly in Cretaceous Spanish amber provides insights into the evolution of integumentary specialisations on the raptorial foreleg - Pérez-De La Fuente, R; Peñalver, E (Nature Research, 2019)
Multiple predatory insect lineages have developed a raptorial lifestyle by which they strike and hold prey using modified forelegs armed with spine-like structures and other integumentary specialisations. However, how structures enabling the raptorial function evolved in insects remains largely hypothetical or inferred through phylogeny due to the rarity of meaningful fossils. This is particularly true for mantidflies (Neuroptera: Mantispidae), which have a scarce fossil record mostly based on rock compressions, namely isolated wings. Here, Aragomantispa lacerata gen. et sp. nov. is described from ca. 105-million-year-old San Just amber (Spain), representing the oldest and one of the few mantidflies hitherto described from amber. The fossil shows exquisitely preserved forefemoral spine-like structures composed of integumentary processes each bearing a modified seta, and prostrate setae on foretibiae and foretarsi. The fine morphology of these structures was unknown in fossil mantidflies. An assessment of integumentary specialisations from raptorial forelegs across mantispoid lacewings is provided. The present finding reveals how the specialised foreleg armature associated to the raptorial lifestyle in extant mantidflies was present yet not fully established by the Early Cretaceous, at least in some lineages, and provides palaeontological evidence supporting certain evolutionary patterns of acquisition of integumentary specialisations related to the raptorial function in the group.